2001
DOI: 10.1071/ea00153
|View full text |Cite
|
Sign up to set email alerts
|

Improving the pre-weaning nutrition of calves by supplementation of the cow and/or the calf while grazing low quality pastures. 2. Calf growth, carcass yield and eating quality

Abstract: Tender, juicy and flavoursome are desirable meat traits in the grading system of Meat Standards Australia. There are 3 critical growth phases affecting these traits in domestic trade cattle: birth to weaning (phase I), weaning to feedlot entry (phase II), and feedlot finishing (phase III). In the study reported in this paper we examined the effects of supplementary feeding of cows and/or calves in phase I on calf growth rate during each of the 3 growth phases and assessed whether differences in early growth we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…During the pre-weaning period, the heifers from the WLP-A rearing management had an average daily gain (ADG) lower than those from the WLP-E [10]. According to the results of Hennessy et al [39], the meat flavor intensity was lower when cattle had a quick growth before weaning. Our results are not in accordance with these results.…”
Section: Resultsmentioning
confidence: 99%
“…During the pre-weaning period, the heifers from the WLP-A rearing management had an average daily gain (ADG) lower than those from the WLP-E [10]. According to the results of Hennessy et al [39], the meat flavor intensity was lower when cattle had a quick growth before weaning. Our results are not in accordance with these results.…”
Section: Resultsmentioning
confidence: 99%
“…Bispo et al [ 37 ] found that nursed calves were characterized by higher BW gains and their meat was juicier, compared with calves that could not suckle from their mothers. In contrast, Hennessy et al [ 38 ] demonstrated that samples of the longissimus lumborum et thoracis muscle originated from calves showing lower growth rates before weaning had a better tenderness than those from animals which had higher growth rates. In this study, meat from C calves had a somewhat higher IMF content than meat from R calves (0.09% and 0.2%, a non-significant difference), which could partially explain the observed difference in meat juiciness.…”
Section: Discussionmentioning
confidence: 99%
“…Although Peterson et al (1992) and Craine et al (2009) showed improved forage quality during drought conditions, this may not be representative of negative changes in diet quality related to reduced plant growth and yield ( Laude, 1953 ). A reduction in overall diet quality or availability can reduce maternal milk yield and calf weaning BW ( Neville, 1962 ; Jenkins et al, 2000 ; Hennessy et al, 2001 ). The impacts of preweaning nutrient restriction (reviewed by Greenwood and Café (2007) ) or any nutritional management that affects growth and development before the finishing phase, such as early weaning (reviewed by Schmidt and Olson (2007) ) or grazing low-quality forage postweaning (reviewed by Drouillard and Kuhl (1999) ), can affect physiological processes much later in an animal’s life resulting in altered feedlot growth and carcass composition.…”
Section: Discussionmentioning
confidence: 99%